Predictor factor of inguinal lymph lode metastasis in men with penile cancer at Sanglah General Hospital, Denpasar, Bali - I. Wayan Yudiana; Gede Wirya Kusuma Duarsa; Anak Agung Gde Oka; Kadek Budi Santosa; Pande Wisnu Tirtayasa; Harmaya AK; Wahjoe Djatisoesanto (PAGEPress Publications, 2019)
Background: To know predictor factors of inguinal node metastasis in penile cancer. Methods: A retrospective study about penile cancer in Sanglah Hospital, Bali, from 2011 to 2015. Patients had undergone partial or total penectomy, and inguinal node dissection or excisional biopsy for histopathology finding. Results: A 65 penile cancer patients were diagnosed for 5 years. Mean age was 53,24 ± 13,42 years. Fifteen were excluded and 25 of 50 patients (50%) had inguinal node metastasis. There were significant correlation between pathologic stage (p=0,021), histologic grade (p=0,020) and vascular invasion (p=0,008) with the presence of inguinal node metastasis. Primary tumor of pT1 showed 14% inguinal node metastasis compared to pT2 (42%), pT3 (67%), and pT4 (100%). Histologic grade I, had 22% inguinal node metastasis compared to grade II (50%), and grade III (100%). Only 39% patients without vascular invasion had inguinal node metastasis compared to 83% with vascular invasion. Conclusion: Pathologic stage of primary tumor, histologic grade and vascular invasion were predictor factors of inguinal node metastasis in penile cancer.